IMPLEMENTASI PENGAWASAN DANA PENDIDIKAN SEKOLAH NEGERI DI PROVINSI JAWA BARAT WILAYAH XIII - Rini Indah Sari Sari; Irfan Afandi (Cross-Border Journal of Business Management, 2023)
This study aims to describe and analyze the implementation and management of education finance. The implementation of school education financial management is carried out and carried out the function of education finance, especially the management of BOS funds, and even then it is still constrained carefully before BOS funds are received and the slow disbursement of funds from policy determinants that affect the next program. In accordance with this fact, the author suggests that it is better to implement school financial management, especially in the management of BOS funds, to improve the management system in administrative management, especially in the collection of pedagogic data to complete the BOS admission requirements funding for the school so that plans can be implemented and the principal's skills to find other sources of funding to overcome the limitations found.